Hazelnuts: a valuable resourece - Guiné, Raquel (2020)
Hazel (Corylus avellana L.) nutshell is one of the most consumed and most appreciated nut fruit all over the world. It is believed to have constituted a basic food in early prehistory, in temperate zones of the globe, such as for example Europe. Presently the hazelnut production is mainly concentrated on the Black Sea coast of Turkey, but other countries are also important producers, like for example Portugal, situated on the western Europe, in the Iberian Peninsula. The objective of this talk is to make a review about the worldwide importance of hazelnut, their usages, including gastronomic and industrial applications, as well as some ways that allow adding value to this fruit, making it an even more valuable resource. The advantages include higher income for produces, lower environmental impacts and valorisation of residues improving sustainability and providing valuable products for consumers and/or ingredients to incorporate into those products.